Classification of adult‐type diffuse gliomas: Impact of the World Health Organization 2021 update. (14th March 2022) - Whitfield, Benjamin T.; Huse, Jason T.
Abstract: Over the last decade, developments in molecular profiling have radically altered the diagnosis, classification, and management of numerous cancer types, with primary brain tumors being no exception. Although historically brain tumors have been classified based on their morphological characteristics, recent advances have allowed refinement of tumor classification based on molecular alterations. This shift toward molecular classification of primary brain tumors is reflected in the 2021 5 th edition of the WHO classification of central nervous system tumors (WHO 2021). In this review, we will discuss the most recent updates to the classification of adult‐type diffuse gliomas, a group of highly infiltrative and largely incurable CNS malignancies. It is our hope continued that refinement of molecular criteria will improve diagnosis, prognostication, and eventually treatment of these devastating tumors. Abstract : The 2021 5th edition of the WHO classification of central nervous system tumors (WHO 2021) further solidifies the centrality of molecular markers in the classification of adult type diffuse gliomas, generating 3 primary diagnoses: IDH‐mutant, 1p/19q codeleted oligodendroglioma; IDH‐mutant, non‐codeleted astrocytoma; and IDH‐wildtype glioblastoma. These changes represent a step towards more uniform disease entities, thereby enabling rational clinical decision making and advancing the field toward a future of distinct and targetable, molecularly‐defined disease entities.